A review on empowering farmers through technology adoption towards poverty alleviation in developing countries - Herath, Muthubandage Mahinda; Ahmad, Nobaya; Hassan, Mohammad Mujaheed; Wan Jaafar, Wan Munira (Human Resource Management Academic Research Society, 2021)
Poverty alleviation is critical to improving the living standards of communities that earn less than $1 per day; the majority of them work in agriculture in developing countries. Lack of technological adoption is a significant factor influencing agricultural performance and minimizes the income of the poor rural community in many developing countries. The primary goal of this paper is to empirically validate the link between empowerment and technology adoption in the context of poverty alleviation. The current study conducted a review study to assess the influence of empowerment and technology adoption on poverty alleviation within the agricultural community in developing nations from 2010 to 2020, identified 11 studies that fulfilled our inclusion criteria. Technology adoption can empower individuals and alleviate poverty in many ways. The cumulative impact of technology interventions on empowerment is determined by how these factors interact independently and cohesively. Improved technology adoption is essential, but it is not enough to prevent poverty at the domestic level. Agriculture science and technology, community development approaches, policies, and systematic structure need to address poverty alleviation. The empowerment approach provides a holistic vision of sustainable community development. Finally, empowerment is essential for poverty alleviation through technology adoption in developing countries.